Electrolichas circumbalticus gen. et sp. nov. (Coleoptera: Byrrhoidea: Ptilodactylidae) from Baltic amber, the first anchytarsine toed-winged beetle described from Europe - Alekseev, Vitalii I.; Jäch, Manfred A. (Zootaxa, 2016)
A new genus and species of Ptilodactylidae, Electrolichas circumbalticus gen. et sp. nov., the first fossil representative of the subfamily Anchytarsinae, is described from Baltic amber. This Eocene beetle can be distinguished from the extant genera of Anchytarsinae by the combination of the following characters: labrum transverse, terminal segment of maxillary palps cylindrical, antennae with non-articulated rami, basal pronotal margin only very finely crenulate, lacking a median denticle, anterior margin of scutellum not excised medially, elytra not striate, tarsi not pseudotetramerous, proportional lengths: 1.5: 1.2: 1.2: 1.1: 1.5, flashy pads on apex of first tarsomere as well as on tarsomeres 2–4. A list of the extant species of Anchytarsinae is provided. Both hitherto described fossil ptilodactylid genera are briefly discussed.